PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Putri Silkatin Nafi ah; Iman Karyadi (CV. Denasya Smart Publisher, 2026)
The study aims to test and analyze the influence of Capital Structure, Profitability, and Company Size on the Firm Value of Mining Sector Companies listed on the Indonesia Stock Exchage. This research is classified as quantitative research. The population analyzed in this study consists of companies in the Basic Materials sub-sector listed on the Indonesia Stock Exchage for the period 2022-2024. This study used purposive sampling, with a sample of 114 samples obtained from 38 companies. The research method used was multiple linear regression analysis with the application of SPSS 23. The results of this study indicate that Capital Structure has no effect on Firm Value, Profitability has a significant effect on Firm Value, and Company Size has no effect on Firm Value.